As quebradeiras de coco babaçu e suas metamorfoses discursivas - SILVA, Edson Sousa da (2021)
This dissertation aims to analyze the construction of the identity of the babassu coconut breakers and their metamorphoses from the discourse present in the Foundation Acts and Social Statutes of the Association of the Interstate Movement of Babassu Coconut Breakers (MIQCB) based in São Luís – MA and operating in the states of Pará, Piaui, Tocantins and Maranhão, of the Association of Rural Women Workers of Babassu Coconut Breakers of the Municipality of São Luís Gonzaga (AMTQC) and the Association of Rural Women Workers (AMTR). The process of organizing the babassu coconut breakers, since the 1980s, defines as a framework for this dissertation, the corpus used brings the history of their organization, considering: the themes debated by the subjects over the years, the present discourses, their form of organization and the relationship with the State apparatus. The discourse of the babassu coconut breakers who are women whose survival is based on plant extraction, with the collection and sale of products from the vegetation called Babassu Forest, which provides the basis for the process of struggle and affirmation of their identity. They are organized into groups of mothers, associations, movements, and cooperatives. There are approximately 300,000 women who survive and have their lives surrounded by the extraction of the babassu fruit. As a methodology, we used the survey and analysis of the books of founding Minutes and Social Statutes of the referred associations, which make up the research corpus. As theories that helped in the analysis of the corpus, we have about the Althusser ideology (1970) in the debate about the notions of discursive formations by Michel Foucault (2012), about the points in which the discourses build the identity of the babassu coconut breakers, concepts of Hall (1998), Giddens (2002) and Bauman (2005), on the discursive image of coconut breakers Maingueneau (2018) and Charaudeau (2009) on discursive identity. The conclusions of this work show that the babassu coconut breakers' discourses focus on the continuation of work by young people and the difficulties that continue with the culture of subjects for the new generations. It cannot be affirmed that there is an identity of the babassu coconut breakers built, ready and finished, but it is evident that there is an approximation with the concept of ethos to understand the represented or self-identified discursive image. Although, the concept of identity “rural workers babassu coconut breakers” is expanding and differentiates individuals according to their territories, as there are indigenous coconut breakers, maroons, and even riverside dwellers.